"I would not have taken her for his sister": financial hardship and women's reputations in the Hartlib circle (1641-1661). Issue 1 (2nd January 2022) - Bourke, Evan
ABSTRACT: Scholarship on transnational correspondence networks has until recently tended to focus on men's intellectual endeavours. While the first phase of feminist scholarship focused on recovery of women's voices, this article argues that incorporating the epistolary reception of women writers (letters written about women writers) enriches our understanding of women's experiences in these networks. It brings attention to the ways in which women were perceived by other (usually male) correspondents, and the boundaries imposed on women in order to be accepted. By focusing on the Hartlib circle, this article highlights the experiences of Dorothy Moore (c.1613–1664) and Jean Appelius (fl. 1638–1648), and showcases the way women's reputations were inseparable from financial realities.